Introductory algebra - Strnad, Wayne A. (Boston, Massachusetts : Prindle, Weber & Schmidt, 1987)
This book is the result of over 10 years of teaching algebra and developmental mathematics in a wide variety of educational environments.
Chapter 1. Mathematics as a living experience -- Chapter 2. Evaluating and simplifying algebraic expressions -- Chapter 3. Solving equations and inequalities -- Chapter 4. Exponents and polynomials.
Includes index.
Keywords: ALGEBRA